Branding Strategies of Horizontal International Mergers and Acquisitions A Case Study of a Finnish Global Company - Wang, Yichen (My University, 2011)
The study is inspired by the increasing population of global IMA, and the missing of sufficient researches on branding strategies influences on IMA performances. The research question is ''how branding strategies influence horizontal IMA performances’’, which expanded into three research objectives. First objective is to identify horizontal IMA and different motivations behind the decision, as well as the different performance valuation of the companies. Second objective is to define and understand key elements in branding strategies, such as its definitions, types, structures, differences, as well as rebranding after mergers and acquisitions, and discuss the branding strategies within IMA context. Last objective is to empirically study the influences of branding strategies on a Finnish B2B company during its globalization approaches through IMA. The theoretical framework is formed after Chapter 2 and Chapter 3, to build up the relationship between two main elements: branding strategies and horizontal IMA. This study follows qualitative research method. The data is collected from a selected case company through analyzing three IMA cases in a global context. Interview is the main method to gain data, with the complementary of information from company website, annual reports, and company partner websites for the purpose of including as objective data as possible. The empirical part of the study is focused on the three real IMA cases of a Finnish B2B global company during its international expansion approaches. The finding is that the branding strategies have to adapt to company key value and the core business. The standardization is not an essential factor to insure cost deduction, but building strong brand equity or buying valuable rare brand assets have positive influences on company gaining competitive advantages, sustainability growth, and enhancing brand image and synergy given a skillful management handling. However, the same branding strategy might have different influence on IMA performance referring to different products and various industrial environments.
Keywords: International mergers and acquisitions; Performance; Branding strategy; Brand architecture; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|